Increment of Steel Tonnage for Reinforced Concrete School Building Considering Seismic Design - H. A., Roslan; M. I., Adiyanto; S. A. H. S., Mustapa; T. A., Majid; N. S. H., Harith (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
A series of Indonesian earthquakes, especially from Sumatra caused vibration on buildings in Peninsular Malaysia like Kuala Lumpur and Penang Island. In East Malaysia, Sabah state has been classified as a region with active local seismic fault. A moderate earthquake with Mw6.1 was occurred in Ranau on 5th June 2015 and caused damage on buildings either the structural or non-structural members. Hence, the implementation of seismic design on new buildings is important to ensure public safety. However, such action has its own pro and contra especially when dealing with cost. Therefore, current research work presents the influence of seismic design consideration on the increment of cost for steel reinforcement. For that purpose, a four storey reinforced concrete school building was generated and used as basic model for analysis, design, and taking off. Two level of seismicity representing by the reference peak ground acceleration, αgR equal to 0.07g and 0.10g has been taken into account in the structural analysis and seismic design process. Besides, three soil type namely as soil type A, soil type C, and soil type E also has been considered as variable parameter. Based on result, total steel tonnage in beams for models considering seismic design increases around 14% to 119% higher than the model without seismic design. For columns, the increment is around 13% to 155%. Generally, total cost of steel used as for concrete reinforcement of the whole structure increases around 13% to 131% depending on the level of seismicity and soil type.